Harnessing ICT Resources: Empowering Educators and Enhancing Student Skills Through Teacher Training Programs (Journal of Asian Development Studies, 2024)
Incorporating Information and Communication Technologies (ICT) into educational settings has fundamentally transformed pedagogical practices; however, the effective implementation of these technologies within teacher training programs continues to pose significant challenges. This systematic review examines the role of ICT resources in the professional development of educators and their influence on the enhancement of student competencies, with particular attention to frameworks such as the Technological Pedagogical Content Knowledge (TPACK) and the Digital Competence Framework for Educators (Dig Comp Edu). By synthesizing findings from various studies, the review reveals emerging trends, including an increasing focus on digital literacy, critical thinking, and collaborative learning, while acknowledging obstacles such as insufficient infrastructure and limited training opportunities for teachers. The results indicate the transformative potential of innovative technologies, including artificial intelligence and virtual reality, in redefining educational methodologies. Nonetheless, the review highlights notable deficiencies, particularly the necessity for quantitative research to assess the direct effects of ICT on educational outcomes and the restricted scope of teacher training initiatives in addressing contextual challenges. This review highlights the transformative potential of ICT integration in teacher training programs and its essential role in enhancing student skills. The evidence synthesis indicates progress in developing teachers' ICT competencies but also reveals persistent challenges, such as infrastructural inadequacies and a lack of comprehensive quantitative assessments. Recommendations include the formulation of inclusive ICT policies, the expansion of teacher training programs, and the promotion of equitable access to technology in under-resourced areas. This study offers practical insights for educators, policymakers, and educational institutions, underscoring the critical importance of strategic ICT integration to prepare students for the challenges of the 21st century adequately. Future research should prioritize longitudinal studies and investigate the role of ICT in fostering inclusivity and personalized learning experiences.